PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, SISTEM PENGENDALIAN INTERN PEMERINTAH DAN PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH PROVINSI PAPUA - Erwin Siahaya; Meinarni Asnawi; Paulus K. Allo Layuk (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2018)
The purpose of this study is to examine and analyze the influence of competence of human resources, government internal control system and the application of regional financial accounting system to the quality of local financial statements. The population is a financial administration staff of 49 SKPD, while the sample amounted to 120. Data collection was done by direct survey. Hypothesis testing is empirically tested using Multiple Regression. The results of partial research on the quality of human resources have a positive effect on the quality of financial statements. The government's internal control system has a positive effect on the quality of local government financial reports. Other findings of the local government accounting system have a positive effect on the quality of local government financial reports. While the results simultaneously have a positive and significant effect on the quality of the Government's financial statements. Keywords: Human Resources Competency, Government Internal Control System, Application of Local Financial Accounting System and Quality of Regional Financial Report.